Actin Distribution in Lamina Neuralis During Cranial Neurulation of Wistar Rats Embryo (Rattus rattus) - Indriayuni Prahastuti; S.M. Issoegianti R. (Indonesian Journal of Biotechnology, 2008)
such as craniorachisis and exencephaly. One of the processes is changing in lamina neuralis cells shape, which iscaused by actin microfilament rearrangement within lamina neuralis cells. To examine the distribution of actinmicrofilament during cranial neurulation Wistar rats embryo were used. Embryos were obtain at following days ofdevelopment; 8 days 18 hours, 9 days, 9 days 6 hours, 9 days 12 hours, 9 days 18 hours, and 9 days 20 hoursrespectively. Immunohistochemistry Avidin Biotin-peroxidase Complex (ABC) method was used to examine andidentify the distribution of actin in lamina neuralis cells. Light microscopic observation shows positive reaction foractin immunoreactivity in the apical surface of bending lamina neuralis cells. In contrast, actin is not observed in nonbendinglamina neuralis. Actin is not detected at 8 days 18 hours embryos. At 9 days embryos, positive reaction isobserved over the entire apical surface of lamina neuralis.Key words: Cranial neurulation, Actin, lamina neuralis, Rats embryo.